2022
DOI: 10.3390/v14040720
|View full text |Cite
|
Sign up to set email alerts
|

Exercising the Sanger Sequencing Strategy for Variants Screening and Full-Length Genome of SARS-CoV-2 Virus during Alpha, Delta, and Omicron Outbreaks in Hiroshima

Abstract: This study aimed to exercise the Sanger sequencing strategy for screening of variants among confirmed COVID-19 cases and validate our strategy against NGS strains in Hiroshima retrieved from GISAID. A total of 660 samples from confirmed COVID-19 cases underwent screening for variants by Sanger-based partial sequencing to the targeted spike gene (nt22,735~nt23,532) using an in-house-developed primer set. The identification of variants was done by unique checkpoints of base nucleotide changes in the targeted spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…We excluded HD patients with COVID‐19 who were treated on an outpatient basis. In December 2021, the Omicron variant (B1.1.529) was detected, and in January 2022, most were infected with the Omicron variant (B1.1.529) (89%), followed by the Delta variant (B1.1.617) (11%) in Hiroshima in Japan [16]. Therefore, the study period coincided with the Omicron epidemic.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded HD patients with COVID‐19 who were treated on an outpatient basis. In December 2021, the Omicron variant (B1.1.529) was detected, and in January 2022, most were infected with the Omicron variant (B1.1.529) (89%), followed by the Delta variant (B1.1.617) (11%) in Hiroshima in Japan [16]. Therefore, the study period coincided with the Omicron epidemic.…”
Section: Methodsmentioning
confidence: 99%
“…Third, we could not test specific SARS-CoV-2 strains in each subject, instead, patients were categorized into groups based on the epidemic periods of each strain as reported in Hiroshima. 19 Fourth, we conducted this study using self-administered questionnaires, which introduces the potential for both underestimation and overestimation of the impact of post-COVID-19 symptoms. Fifth, this study questionnaire did not include an assessment of symptom severity or the impact of post-COVID-19 symptoms on the daily lives of patients.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate variant-specific symptoms following COVID-19, participants were grouped into four categories based on their symptom onset date and the monthly distribution of the dominant variant in Hiroshima Prefecture. 19 These groups were designated as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Their later study also pointed out that the genomic information coverage among confirmed COVID-19 cases is too low when using NGS. It reiterated the usefulness of Sanger sequencing not just in understanding variant distribution over time but also in providing evidence for policy making and the formulation or modification of preventive strategies [ 14 , 15 ]. In this study, a similar Sanger-based approach was adapted to a much smaller setting, like our non-COVID hospital.…”
Section: Discussionmentioning
confidence: 99%